Comparative Effects of Nigella Sativa and Cassia Senna in Iron Overloaded Mice - Uzma Naeem, Rabia Azhar, Wajiha Shadab, Nazir Awan, Maryam Naeem, Jawairia Iftikhar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Iron overload-related complications are the main concern in patients who must often receive blood transfusions. The only way to treat iron overload in these patients is by chelating agents. Owing to the high cost and adverse effects of chelating agents use of naturally present chelators is under study. Aim: To compare the protective effects of two commonly used herbs Nigella Sativa and Cassia Senna in iron-overloaded mice. Study Design: Experimental randomized controlled trial. Setting: Zoology department of Govt College University Lahore during six months period. Method: A total of forty-eight mice were divided into four groups (n = 12). Group one was normal to control while group 2, 3, and 4 were overloaded with iron by intravenous injection of iron dextran (0.1 ml/kg body weight) daily for fifteen days. After 15 days iron overload was confirmed by blood testing. For additional 15 days, group three mice were provided with Cassia Senna (100 mg/Kg body weight) while group four mice were permitted to feed on Nigella sativa (200 mg/Kg body weight). Animals were sacrificed on day 32 and organs were preserved to check the iron levels. Blood sampling was done on days 0, 15, and 31 to analyze serum iron levels. Results: The protective effect of Nigella Sativa was more marked than cassia senna in iron 0verloaded mice. Conclusion: The addition of Nigella Sativa instead of cassia senna in iron-laden patients as an adjunct therapy can be more beneficial in preventing the damaging effects of iron overload.